Training of Health Professionals in Intercultural Competencies (Andamios, Revista de Investigación Social, 2026)
This theoretical article discusses epistemological challenges for training health professionals in intercultural competencies in La Araucanía, Chile. The problem relates to professional training based on scientific knowledge as the sole and true means of understanding health, which denies and omits the existence of other forms of knowledge, limiting interventions with sociocultural relevance. It is argued that even when intercultural health policies are promoted within the health system, they are based on an interculturality that serves the interests of a neoliberal state. This poses the challenge of rethinking the training of health professionals so that they are capable of operating from a perspective of social, cultural, and territorial relevance in their professional work.
Keywords: Primary health care; cultural competence; cultural diversity; higher education; health students